Interacción del virus de la fiebre aftosa con las células dendríticas: génesis de la respuesta inmune adaptativa - Langellotti, Cecilia Ana (2012)
Foot-and-mouth disease is a highly contagious and acute viral disease of cloven-hoofed animals, caused by Foot-and-Mouth Disease Virus (FMDV). It is\ncharacterized by fever and vesicular injuries located in oral cavity, tongue and all\naround the hooves. From an economical point of view, it is the most important\ndisease of livestock worldwide. The economic consequences of the infection are more generated by physical and productive deterioration, than by mortality, but for\ncountries who export animals and its products, as Argentina, the main losses are due to strong restrictions imposed to the international trade. The FMDV interacts with dendritic cells, both in the natural host and in mice,\nbut the impact of this interaction on the adaptive immune response is controversial. Currently available vaccines are based on inactivated forms of the FMDV. Little is known about the differences between infectious and inactivated virus, in terms of dendritic cell subsets involved in immune response activation. The present work, which was carried out in the mice model, shows that live virus infection induces a\nreduction in splenic dendritic cell subsets. In addition, lymphocyte proliferation is\ninhibited in the early stages of infection, but restored to normal values 5 days postinfection. By contrast, the inactivated virus increases the percentage of\nplasmacytoid dendritic cells in the spleen and the production of IL-10, which\ntriggers the activation of a T regulatory response.\nThe present work, which was carried out in the mice model, shows that live\nvirus infection induces early immunosuppression at level of reduction in the\nnumber of splenic dendritic cell subsets, and the inhibition of activation and\nmaduration of them. In addition, infection induces the secretion of low levels of\nIFN-a in pheripheral blood. Lymphocyte proliferation is inhibited in the early stages\nof infection, but it is restored at 5 days post-infection. By contrast, the inactivated\nvirus increases the percentage of plasmacytoid dendritic cells in the spleen and the production of IL-10, which triggers the activation of a T regulatory response